2021
DOI: 10.1002/advs.202103693
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular DNA: A Missing Link in the Pathogenesis of Ectopic Mineralization

Abstract: Although deoxyribonucleic acid (DNA) is the genetic coding for the very essence of life, these macromolecules or components thereof are not necessarily lost after a cell dies. There appears to be a link between extracellular DNA and biomineralization. Here the authors demonstrate that extracellular DNA functions as an initiator of collagen intrafibrillar mineralization. This is confirmed with in vitro and in vivo biological mineralization models. Because of their polyanionic property, extracellular DNA molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…refs. 14 and 38 ) together with our observation that exogenous DNA is capable of inducing precipitation in cell-free medium would suggest the direct involvement of the negatively charged eDNA molecules in Ca 2+ recruitment and precipitation. At the same time, the contribution of microenvironment in ECM as well as involvement of amyloids in nucleation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…refs. 14 and 38 ) together with our observation that exogenous DNA is capable of inducing precipitation in cell-free medium would suggest the direct involvement of the negatively charged eDNA molecules in Ca 2+ recruitment and precipitation. At the same time, the contribution of microenvironment in ECM as well as involvement of amyloids in nucleation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 69%
“…Besides the role in formation of the protein component of ECM, glyceraldehyde-3-phosphate dehydrogenase has been shown to act as a regulator of biofilm formation in a representative of B. cereus by triggering the formation of extracellular DNA 38 . In the calcium- and urea-free medium B4 , we observed eDNA in relatively small quantities and only at the later stages of the growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to organic materials, using this method gives biological organisms (e.g., cells and virus) a mineralization layer to make them have higher viability than native ones in a lot of hostile conditions, including longtime exposure to salt water, elevated temperature, ultraviolet light, lyticase, and osmotic pressure. , For instance, periplasmic carbonic-anhydrases contribute to the biomineralization of nanofibrous calcium carbonate in the stalks of Didymosphenia geminate for better stability in various hydrodynamic conditions; extracellular polysaccharides in Chlorella and Scytonema exhibit templating activity toward hydrozincite biomineralization to prevent cell entombment . Although sometimes extracellular macromolecules may cause ectopic mineralization in body tissues, the mechanism is still inspiring for fabricating useful inorganic–organic hybrid materials . By mimicking the biomineralization processes in organisms that can survive in various environments, artificial composite materials can be developed for use in the extremes of modern industries .…”
Section: Introductionmentioning
confidence: 99%
“…43 Although sometimes extracellular macromolecules may cause ectopic mineralization in body tissues, the mechanism is still inspiring for fabricating useful inorganic−organic hybrid materials. 44 By mimicking the biomineralization processes in organisms that can survive in various environments, artificial composite materials can be developed for use in the extremes of modern industries. 45 The key to engineering molecular bridges is to gather functional groups that provide strong anchors to glue organic materials and reliable sites for the immobilization and growth of inorganic species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It should be noted that the metastable ACP phase can be stabilized well in aqueous solution using appropriate additives ( Manuel Delgado-Lopez et al, 2017 ; Mao et al, 2021 ; Ruiz-Agudo et al, 2021 ) and/or ions ( Ding et al, 2014 ). There are numerous excellent previous studies focusing on the regulation of calcium phosphate with various morphologies, such as by adding polymers ( Yao et al, 2019 ), citric acid ( von Schirnding et al, 2021 ), oleic acid ( Li et al, 2017 ), and nucleic acid ( Shen et al, 2021 ). It has been demonstrated that the formation of calcium phosphate can be influenced by the polarity, molecular weight, and electric groups of polymers ( Schweizer and Taubert, 2007 ).…”
Section: Introductionmentioning
confidence: 99%